Asociación entre tiroiditis crónica y cáncer diferenciado de tiroides. Revisión de la literatura. - Lanas M., Alejandra; Cordero A., Francisco (Revista Hospital Clínico Universidad de Chile, 2011)
Differentiated thyroid cancer (DTC) in the common endocrine malignancy. Its frequency increases with age and its have a female predominance. There is evidence that papillary thyroid cancer is increasing in recent years. It has been proposed that this increase is independent from the greater availability of diagnostic techniques, because is observed an increase in both small tumors like those of grater size and more advanced stage. The causes of this increase are unclear and several hypotheses have been raised, including within these possible factors the presence of chronic thyroiditis (CT). Among the reasons to make this association is the relationship described between inflammatory processes and the genesis of cancer as well as some descriptive studies that reports a high incidence of CT in patients with DTC. But the results of these studies are controversial and there are other reports in rejecting this association.